Optimasi Pengaruh Waktu Kontak dan Dosis Adsorben Limbah Daun Kayu Putih (Melaleuca cajuputi) dengan Metode Isoterm Adsorpsi Langmuir - Kusumaningrum, Dinar Ika Pambudi; Sudarni, Dyan Hatining Ayu; Wahyuningsih, Sri (Talenta Publisher (Universitas Sumatera Utara), 2022)
Liquid waste from the textile industry contains harmful dyes that can damage the environment. Pollution to the environment can be minimized by processing dye waste before being discharged into rivers or sewers. The dye waste treatment process can be carried out using the adsorption method. The adsorbent used was non-activated and acid-activated eucalyptus leaf waste (HCl 2 M). The solution used as adsorbate is malachite green. This study aims to optimize the absorbance level of eucalyptus (Melaleuca cajuputi) leaf waste against malachite green dye using the Langmuir adsorption isotherm method. The variables used are the mass variation of the adsorbent, the contact time and the adsorption isotherm model. The absorption efficiency value produced by the adsorbent of eucalyptus leaf waste with 2 M HCl activation was 87.4279%. Meanwhile, the non-activated adsorbent is 86.0290%. For time variations of 10 minutes, 15 minutes and 20 minutes on 2 M HCl activated adsorbent resulted in an absorbance of 0.026; 0.022; and 0.02. Based on the graph of the relationship between Ce and Ce/Qe for the non-activated adsorbent, R2 was obtained at 0.7039 while the 2 M HCl activation was 0.966. So, the eucalyptus leaf waste can be used as an adsorbent without a carbonization process, only needs to be given activation treatment using an acid solution.